The Valuation of Rhytidectomy in Different Economic Markets - Kumar, Anisha R.; Ishii, Lisa E.; Papel, Ira; Kontis, Theda C.; Chen, David; Liao, David; Chen, Jonlin; Nellis, Jason; Ishii, Masaru (Facial Plastic Surgery, 2020)
This study demonstrates that the trend of how rhytidectomy is valued can be used to determine not only the pricing of this good but also how receptive developing economic markets are to the export of cosmetic facial plastic surgery. This study seeks to analyze and compare the value of rhytidectomy in an established market and an emerging market. A cross-sectional survey was administered through public online forums to 162 casual observers in the United States and 74 casual observers in India. Participants were shown pre- and postoperative photos of 10 patients who underwent cosmetic rhinoplasty and 2 patients who did not undergo surgery. Observers were asked to quantify the perceived change in attractiveness, change in age, and willingness to pay (WTP). There is a similar nonlinear trend between WTP and change in attractiveness in both the United States and India. Baseline values of rhytidectomy in the United States and India have a similar ratio of 2.122 compared with the ratio between both countries in the 2018 Big Mac index. The comparison of the trend in WTP in the United States and India shows that facial cosmetic surgery functions as a luxury good in both an established market and an emerging market. Our model successfully approximates the relationship between each country's purchasing power parity. Since the market behavior of rhytidectomy can be predicted based on purchasing power parity, there may be an untapped market for facial cosmetic surgery among populations with growing economies.
Keywords: rhytidectomy; economy; markets